2004
DOI: 10.1016/j.rmed.2003.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Depression and pulmonary function in outpatients with asthma

Abstract: The purpose of this study was to examine the relation between depression, anxiety and pulmonary function in asthmatics. Thirty-eight adult asthmatic patients underwent psychometric evaluation with the DSSI/sAD questionnaire, filled in an asthma questionnaire and underwent spirometry. The majority of patients suffered from mild-persistent asthma. Twenty-six reported symptoms of anxiety and 25 reported symptoms of depression. A statistically significant reduction in FEV1 and FEV1/FVC values was observed in asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 23 publications
3
25
1
1
Order By: Relevance
“…The recruitment resulted in the exclusion of a large number of subjects (36%) -similar to numbers quoted in other studies (Harrison, 1998;Krommydas et al, 2004;Strunk et al, 2016). In the subjects who completed the study, no significant physiological or inflammatory worsening of asthma was noted during the putative HSV.…”
Section: Airway Physiologysupporting
confidence: 57%
See 1 more Smart Citation
“…The recruitment resulted in the exclusion of a large number of subjects (36%) -similar to numbers quoted in other studies (Harrison, 1998;Krommydas et al, 2004;Strunk et al, 2016). In the subjects who completed the study, no significant physiological or inflammatory worsening of asthma was noted during the putative HSV.…”
Section: Airway Physiologysupporting
confidence: 57%
“…A survey of over 3,000 adults in the United States showed increased prevalence of panic attacks in those with obstructive lung disease (Goodwin, & Pine, 2002). Similarly, depression and anxiety are over-represented in children (Vila et al, 1999;Sundbom et al, 2016) and adults (Sundbom et al, 2016;Krommydas et al, 2004;Harrison, 1998) with asthma. Stress also has many forms: panic disorders and depression can lead to shortness of breath, which appears to be unresponsive to bronchodilators or traditional eosinophil based anti-inflammatory therapy (i.e.…”
mentioning
confidence: 99%
“…In humans, the possible exacerbated chronic inflammatory response induced by repeated stress may translate to increased long-term damage of the airway and gradual deterioration in function through remodeling (35). It is also speculated that depression could directly influence the autonomic nervous system and act on direct respiratory resistance, symptom perception, and AE (36,37). Other studies also report that risk behaviors such as smoking, physical inactivity, obesity, and health-service seeking associated with depression might influence asthma outcomes (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…The group with severe asthma but good adherence showed a level of psychiatric morbidity inbetween the highest and lowest levels. In another study 26 patients (68.5%) reported symptoms of anxiety and 25 (65.8%) patients reported symptoms of depression (18) In a study, Fritz et al (19) found a significant difference in FEV 1 and FEV 1 /FVC values between asthma patients with and without depressive symptoms, and suggested that this may be associated with a common biological pathway between asthma and depression. There are many studies suggesting that treatment of depression and anxiety in patients with asthma improve control of the disease (20,21).…”
Section: Discussionmentioning
confidence: 94%